1989
DOI: 10.1136/ard.48.7.577
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot analysis of IgM, IgG, and IgA responses to plasmid encoded released proteins of Yersinia enterocolitica in patients with or without yersinia triggered reactive arthritis.

Abstract: SUMMARY The IgM, IgG, and IgA antibody responses of patients with Yersinia enterocolitica 0:3 infection were studied by immunoblotting with plasmid encoded released proteins of Y enterocolitica as the antigens. The results indicate that antibodies of all three classes are most consistently directed against the proteins of molecular weights 25 000 and 36 000. Less than two months after the onset of infection 18 of the 19 patients with yersinia triggered reactive arthritis had IgA class antibodies against the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…However, there is little reason to assume that a plasmidless Y entrrocolitica 0 : 3 would exist in the joints, since the Yersinia persisting in the gut during the chronic stage of infection express plasmid-encoded proteins, indicating the presence of the virulence plasmid (6). Furthermore, immunoblotting analyses with sera of arthritis patients have revealed that the persisting antibody response is directed against a multitude of bacterial epitopes, including plasmid-coded antigens (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is little reason to assume that a plasmidless Y entrrocolitica 0 : 3 would exist in the joints, since the Yersinia persisting in the gut during the chronic stage of infection express plasmid-encoded proteins, indicating the presence of the virulence plasmid (6). Furthermore, immunoblotting analyses with sera of arthritis patients have revealed that the persisting antibody response is directed against a multitude of bacterial epitopes, including plasmid-coded antigens (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…In cases of chronic enteritis, IgA antibodies develop against YopE (23 kDa), YopD (35 kDa), and YopB (41 kDa). IgA antibodies against YopD develop in 90% of reactive arthritis cases (7,26,27). IgG antibodies develop against all outer membrane proteins of Yersinia; but they develop more frequently against YopE (23 kDa), YopB (41 kDa), YopD (35 kDa), and YopH (51 kDa) (8,11,21).…”
Section: Discussionmentioning
confidence: 99%
“…By the second month disappearance of the organism was already clearly associated with the disappearance and decrease of IgA antibodies, whereas persistence of the organism in untreated and treated patients was associated with prolonged circulation of specific IgA antibodies. It was already known from earlier studies1 2 10 that patients with yersinia triggered arthritis have more antibodies, which remain for longer, than patients with uncomplicated yersinia infections.…”
Section: Discussionmentioning
confidence: 99%